A Systematic Assessment of Stable Sr Isotopic Compositions of Vent Fluids in Arc/Back-Arc Hydrothermal Systems: Effects of Host Rock Type, Phase Separation, and Overlying Sediment - Yoshimura, Toshihiro; Wakaki, Shigeyuki; Ishikawa, Tsuyoshi; Gamo, Toshitaka; Araoka, Daisuke; Ohkouchi, Naohiko; Kawahata, Hodaka (Frontiers in Earth Science, 2020)
Variations in the stable isotopic composition of seawater Sr (δ88Sr) is a new tool for estimating the rates of global carbonate sedimentation over geologic time, yet the isotope compositions of the major sources and sinks of Sr to the world oceans are still in need of further constraint. We report δ88Sr values of vent fluids from arc/back-arc seafloor hydrothermal systems in the western Pacific. In the sediment-starved hydrothermal fields of the Manus Basin, Izu-Bonin Arc, and Mariana Trough, the δ88Sr values of end-member fluids for each site showed little variation (0.29–0.30‰) and were close to the average value of oceanic volcanic rocks, reflecting dissolved Sr sourced from host rocks. Chlorine-depleted fluids from phase-separated hydrothermal systems in the North Fiji Basin had the end-member δ88Sr values of 0.26‰, 0.28‰, and 0.29‰. Thus, both sediment-starved and phase-separated vent fluids had the end-member δ88Sr values indistinguishable from or very close to the range of oceanic volcanic rocks. Therefore, the δ88Sr compositions in these hydrothermal sites are controlled predominantly by Sr sourced from host rock with a small influence from secondary mineral precipitation/re-dissolution. Fluids from the sediment-hosted hydrothermal fields of the Okinawa Trough, however, were characterized by low δ88Sr values of approximately 0.22‰ and high 87Sr/86Sr ratios, indicating interactions with sedimentary carbonates. As for the modern oceanic δ88Sr budget, the sediment-hosted sites lower the global hydrothermal δ88Sr. Since both sediment-starved and -hosted hydrothermal systems provide a long-term control on the global Sr cycle, the end-member δ88Sr value is an important constraint on the evolution of Sr cycling in past oceans.